Alternate Dispute Settlement System in KP: Challenges, Opportunities and Options for Improvement - Ahmed, Waqar (Journal of Pakistan Administration, 2021)
The Khyber Pakhtunkhwa (KP) province is bordered by Afghanistan in the north-west, Azad Jammu & Kashmir (AJK) and Gilgit-Baltistan (GB) in the east and north-east, Punjab in the south-east, and Balochistan in the south-west. The region on the western boundary of KP, along the Afghan border, comprises areas formerly known as the Federally Administered Tribal Areas (FATA) which were semi-autonomous until 2018. Covering an area of 39,282 square miles (101,741 km2), KP has a population of 35,519,927 (according to the 2017 census). The province carries a unique culture with strong traditional social structures bound by centuries’ old customary rules. Pakhtuns, being the ethnic majority, are governed by their traditional legal code, the Pukhtunwali. The prime virtues of this code are ‘ghairat’ (self-respect / bravery) and ‘izzat’ (honor). Family and community elders play a key role in communal dealings and in ensuring communal peace and social integrity through an informal justice system called Jirga. Considered an alternate dispute resolution (ADR) mechanism, jirgas sit in a circle that symbolizes equality among all the parties and carry out arbitration and mediation between the parties to resolve disputes. It is often the first resort used by Pakhtuns for resolving conflicts because of its impartiality and provision of swift justice.